A Description of Moral Values in JK Rowling’s Novel Harry Potter and Prisoner of Azkaban and their Application to Indonesian Morality Education - Ainun Ralia; Kasmaini Kasmaini; Indah Indah (AL LUGHAH, 2019)
The research aims to find out the moral value in novel and their application to Indonesia morality education. The object of this research is a novel with title Harry Potter and Prisoner of Azkaban by JK Rowling. This research was using qualitative as the methodology and the data was collected by checklist data sheet as an instrument. The checklist consisted of 21 items which represent the moral value base on its types. This research uses Linda theory. The result of data analysis shows that there are 89 items moral value in the novel and all value can be application in Indonesia morality by using 5 value from Character Education in K13. From the results, it is concluded that people in a novel always bring some value which related to education and teacher need to know how to use it.